Особливості біохімічного гомеостазу та стан еритроцитів у вагітних жінок з невиношуванням, інфікованих хламідіями та мікоуреаплазмами - Шамаєва, О.В. (Таврический медико-биологический вестник, 2011)
Изучение особенностей метаболизма у инфицированных беременных с невынашиванием
свидетельствует о наличии эндотоксикоза у женщин с хламидиозом. У них выявлено повышение
уровня СМП (среднемолекулярных пептидов), КФНК (кислотной фракции нуклеиновой кислоты) и
активности ПОБ (перекисного окисления белков), а также снижение осмотической резистентности
эритроцитов и угнетение эритропоэза. У женщин с микоуреаплазмозом обнаружены изменения,
касающиеся лишь целостности клеточных мембран. Study of peculiarities of metabolism in infected pregnant with prematurity indicates about presence of
endotoxicosis in women with chlamydies. It was revealed the increase of level of MMP (middle molecular
peptides), AFNA (acidic fraction of nucleic acids) and activity of SP (superoxygenation of proteins), and also
the decrease of osmotic resistance of erythrocytes and depression of erythropoiesis. In women with
mycoureaplasmas were revealed the changes, concerning only the integrity of cellular membranes.